Evolutionary history and activity towards oligosaccharides and polysaccharides of GH3 glycosidases from an Antarctic marine bacterium - Marchetti, Alessandro; Orlando, Marco; Bombardi, Luca; Fusco, Salvatore; Mangiagalli, Marco; Lotti, Marina (International Journal of Biological Macromolecules, 2024)
Glycoside hydrolases (GHs) are pivotal in the hydrolysis of the glycosidic bonds of sugars, which are the main carbon and energy sources. The genome of Marinomonas sp. ef1, an Antarctic bacterium, contains three GHs belonging to family 3. These enzymes have distinct architectures and low sequence identity, suggesting that they originated from separate horizontal gene transfer events. M-GH3_A and M-GH3_B, were found to differ in cold adaptation and substrate specificity. M-GH3_A is a bona fide cold-active enzyme since it retains 20 % activity at 10 degrees C and exhibits poor long-term thermal stability. On the other hand, M-GH3_B shows mesophilic traits with very low activity at 10 degrees C (< 5 %) and higher long-term thermal stability. Substrate specificity assays highlight that M-GH3_A is a promiscuous beta-glucosidase mainly active on cellobiose and cellotetraose, whereas M-GH3_B is a beta-xylosidase active on xylan and arabinoxylan. Structural analysis suggests that such functional differences are due to their differently shaped active sites. The active site of M-GH3_A is wider but has a narrower entrance compared to that of M-GH3_B. Genome-based prediction of metabolic pathways suggests that Marinomonas sp. ef1 can use monosaccharides derived from the GH3-catalyzed hydrolysis of oligosaccharides either as a carbon source or for producing osmolytes.